1997
DOI: 10.1021/la9605652
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Adsorption of Lipase fromHumicolalanuginosaon Surfaces with Different Wettabilities

Abstract: The adsorption of Humicola lanuginosa lipase and the activity of the adsorbed lipase were studied as a function of surface wettability. The adsorption was measured by in situ ellipsometry, and the surfaces used were methylated silica surfaces. The activity of the adsorbed lipase was measured after rinsing of the cuvette, i.e., with no lipase in the bulk solution, in situ by the hydrolysis of p-nitrophenyl acetate. The lipase adsorption and activity measurements were made at concentrations of the lipase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
3
26
1
Order By: Relevance
“…The optimal reaction temperature for free T. langinosa lipase is around 35-40°C in a solvent system (10). After silicagranulation, Lipozyme TL IM was relatively stable in the solvent-free system in the range from 55 to 80°C (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The optimal reaction temperature for free T. langinosa lipase is around 35-40°C in a solvent system (10). After silicagranulation, Lipozyme TL IM was relatively stable in the solvent-free system in the range from 55 to 80°C (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Lipozyme TL IM has sn-1,3 specificity and hydrophilic character. It is less expensive than the commonly applied commercial lipase Lipozyme IM (Rhizomucor miehei lipase) and offers an opportunity for industry to reduce the process cost and make the production of low-price plastic fats economically competitive to the conventional chemical randomization.Previously T. lanuginosa lipase was investigated mostly in solvent systems in free-state or immobilized forms (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). From kinetic studies, it was found that immobilized T. lanuginosa lipase had different characteristics depending on the solvent systems and the hydrophobicity of carriers (2,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A part of active sites might thus be buried and inaccessible, leading to a dramatic decrease in the bioactivity compared with the native enzymes. Few attempts to control the enzymatic orientation through tailoring the wetting properties 7 or surface charges 8 of the supports revealed that the rational artificial interference was not infeasible. However, in the approaches already reported, a reactive terminal tag or a protein conjugate had to be used.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the approaches already reported, a reactive terminal tag or a protein conjugate had to be used. 7,8 Recently, efforts have been made toward the orientated attachment of proteins to solid surfaces through electrostatic assembly. [8][9][10] The electrostatic recognition strategy is thus believed to be a simple and biocompatible alternative to control the protein orientation.…”
Section: Introductionmentioning
confidence: 99%